Irinotecan Plus Doxorubicin Hydrochloride Liposomes for Relapsed or Refractory Wilms Tumor - Wang, Juan; Zhang, Lian; Guo, Lanying; Que, Yi; Zhang, Yu; Sun, Feifei; Zhu, Jia; Lu, Suying; Huang, Junting; Wu, Liuhong; Cai, Ruiqing; Zhen, Zijun; et al. (Frontiers in Oncology, 2021)
Purpose The prognosis of relapsed or refractory pediatric Wilms tumor (WT) is dismal, and new salvage therapies are needed. This study aimed to evaluate the efficacy of the combination of irinotecan and a doxorubicin hydrochloride liposome regimen for relapsed or refractory pediatric WT. Patients and Methods The present study enrolled relapsed or refractory pediatric WT patients who were treated with the AI regimen (doxorubicin hydrochloride liposomes 40 mg/m2 per day, day 1, and irinotecan 50 mg/m2 per day with 90-min infusion, days 1–5; this regimen was repeated every 3 weeks) at Sun Yat-sen University Cancer Center from July 2018 to September 2020. The response was defined as the best-observed response after at least two cycles according to the Response Evaluation Criteria of Solid Tumors (RECIST 1.1), and toxicity was evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE 4.03). Results A total of 16 patients (male:female, 8:8) with a median age of 4.2 years (0.5–11 years) with relapsed or refractory disease were enrolled in this study, including 14 patients with relapsed disease and two patients with refractory disease. These patients received 1–8 courses (median, 3 courses) of the AI regimen. Fourteen patients were assessable for response: two with complete response (CR), five with partial response (PR), two with stable disease (SD), and five with progressive disease (PD). The objective response rate was 50% (two CR, five PR), and the disease control rate was 64% (two CR, five PR, and two SD). Seven out of 14 patients (50%) were alive at the last follow-up, ranging from 2.6 to 32.4 months. The median progression-free survival and median overall survival were 3.5 months (range 0.5–12 months) and 8 months (range 1–28 months), respectively. Sixteen patients were assessable for toxicity, with the most common grade 3 or 4 adverse events being alopecia (62%), leukopenia (40%), abdominal pain (38%), diarrhea (23%), and mucositis (16%), etc. No fatal adverse events have been observed, and modest adverse effects can be administered. Conclusion Irinotecan and doxorubicin hydrochloride liposome regimens have positive efficacy on relapsed or refractory pediatric WT with well-tolerated toxicity. A prospective clinical trial is warranted.